Review of the Iranian Parholaspidid mites (Acari: Mesostigmata) with a key to the species - Hajizadeh, Jalil (Zootaxa, 2022)
Six species of Parholaspidid mites were collected from Guilan province in Northern Iran. Gamasholaspis browningi (Bregetova & Koroleva, 1960) is a new record for the Iranian Parholaspidid mite fauna. This paper provides a checklist for Parholaspidid mites species recorded from Iran, with a key for identification of the species.